CORRELATION ANALYSIS BETWEEN INDOOR AIRBORNE BACTERIAL LOAD AND OCCUPANT DENSITY IN HOSPITAL INDOOR AIR - Braide, W.; Ajugwo, G.C; Adeleye, S.A.; Mike-Anosike E.E.; Ndukwe, C.U; Chinakwe E.C. (International Journal of Engineering Technologies and Management Research, 2019)
A study of the quantity and types of airborne bacteria and its correlation with human presence was conducted. Air samples were collected from different units for three days and three sessions (morning, afternoon and evening) for the enumeration and identification of bacterial isolates. Walk-through exercise was also conducted prior to every sampling to gather information on the number of occupants present, activities going on, and room characteristics. Isolation study revealed higher bacterial load in the afternoon and evening sessions; with Male Ward and Operating Theatre recording the highest and lowest bacterial loads respectively, as compared to the morning session that was done immediately after cleaning and before influx of people. The Spearman’s Correlation Coefficient showed a positively direct linear correlation between the bacterial load and occupant population irrespective of the three sessions (r = 0.84, 0.88 and 0.93). Identification study showed that the isolates are representatives of normal microflora of the skin, respiratory and gastro-intestinal tracts which includes the following; Staphylococcus aureus, Staphylococcus epidermidis, Micrococcus roseus, Klebsiella pneumoniae, Proteus mirabilis, Bacillus subtilis, Aspergillus, Penicillium, Mucor, Candida and Fusarium species. The study presents evidence of increased concentration of indoor airborne bacteria due to human presence, movement and activities.